ANALISIS FRAMING PERNYATAAN RESMI PARA AKTOR DALAM KRISIS DI KOMPETISI SEPAKBOLA INDONESIA: KASUS POLEMIK JUARA BHAYANGKARA FC DI LIGA 1 TAHUN 2017 - Narayana Mahendra Prastya (Jurusan Ilmu Komunikasi UTM, 2018)
ABSTRACTThe objetives of this articles is to analyse how the actors that involved in the Indonesian football conflict frame their official statement. The conflict in this articles is the controversy of Bhayangkara FC in competition Liga 1 sesaon 2017. The controversy occurs when Indonesian Football Association’s decision give advantage for Bhayangkara FC to win the league. This decision arouse complain from several Liga 1’s contestant. This articles using frame by Robert N.Entman as analysis tool. The research objets are official statements taken from the actors’ official website. The limitation of the actors’ are : Bali United and Madura United as the league contestant that think the PSSI’s decision is unfair; PSSI as the Indonesian FA, and PT Liga Indonesia Baru (PT LIB) as the competition organizer. The results shows that all parties, except PT LIB, are blaming each other in this case. The official statement by the actors are influenced on their own interest